Fatigue behavior of spot welds - Ertaş, Ahmet Hanifi. (Thesis (M.S.)-Bogazici University. Institute for Graduate Studies in Science and Engineering, 2004., 2004)
The resistance spot welding process is widely used in industry, especially in automotive industry. This type of joining method is used widely because of its simplicity, cheapness and of course reliability which are significant aspects of manufacturing processes. Because the spot welded specimens are used widely in industry, the spot weld fatigue life predictions are very important. So, intense scientific studies have been carried out on this subject for years, especially for the last 30 years. In this dissertation, firstly the spot weld fatigue life prediction methods were reviewed. Secondly, using Material Testing System (MTS) test machine that has closed loop servo-hydraulic control system, the suitable lives for modified tensile shear specimen under different pure tension loads (changing from 210 N to 350 N) were determined experimentally. All experiments were conducted at 1-3 Hz. loading frequency; no effect of frequency is expected in this range. For every load condition, the numbers of cycles to failure were obtained. These experimental studies were carried out for different loads in order to obtain sufficient data to predict the S-N curve behavior. Hence, it can be said that fatigue life predictions of spot welded constructions, which is modified tensile shear specimen in this study, is the main objective of this study.In addition to the experimental study a numerical study has been carried out. inite element model of the tensile shear specimen was generated using ANSYS and the resulting stress distribution discussed.
Keywords: Welding.; Fracture mechanics.